Review: The Discovery and Development of Sildenafil Citrate - Septifani, Eza Azhara; Yetti, Rina Desni; Asra, Ridho (Asian Journal of Pharmaceutical Research and Development, 2021)
Background: Griseofulvin is a fungistatic antifungal drug used to treat dermatophytosis. Dermatophytes that are often found include Trichophyton rubrum, Trichophyton mentagrophytes, Microsporum canis, Microsporum gypseum, Epidermophyton floccosum. Purpose: This review article aims to discuss the drug discovery review of griseofulvin. Data Source: The author created this review article using the literature study method relevant to the purpose of the review. Sources of information from national journals and international journals that are accessed through online sites such as Google Scholar, Research Gate, Science Direct, Springer Link, and NCBI. Key words were used to find the journals, namely griseofulvin, dermatophyte, toxicity. Conclusion: The conclusion of this article is that griseofulvin is used as an antifungal drug containing chlorine from Penicillium griseofulvum isolated against mycelium fungus. This drug is non-toxic, so it is effective and safe to fight various types of fungal infections of the skin such as tinea capitis and remains the drug of choice for dermatophytes.